1996
DOI: 10.33584/jnzg.1996.58.2217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pasture species on internal parasites of lambs

Abstract: Increasing resistance of gastro-intestinal nematode parasites to anthelmintics and consumer resistance to the possibility of residues in animal products have prompted research on the effect of pasture species on nematodes and animal performance. Lambs (either infected with high rates of gastrointestinal nematodes or maintained nematode-free) were grazed on pure swards of chicory, high- or low-endophyte ryegrass, cocksfoot, tall fescue, lucerne, lotus, white clover or plantain. Infected lambs that graze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Plantain also contains a number of biologically active compounds, such as the iridoid glycosides acubin and catapol, which have chemical defense properties in the plant (El‐Niggar and Beal, 1980; Bowers and Stamp, 1992). Plantain and chicory reportedly have medicinal properties in livestock but the research is not conclusive (Knight et al, 1996; Gustine et al, 2001; Marley et al, 2002).…”
mentioning
confidence: 99%
“…Plantain also contains a number of biologically active compounds, such as the iridoid glycosides acubin and catapol, which have chemical defense properties in the plant (El‐Niggar and Beal, 1980; Bowers and Stamp, 1992). Plantain and chicory reportedly have medicinal properties in livestock but the research is not conclusive (Knight et al, 1996; Gustine et al, 2001; Marley et al, 2002).…”
mentioning
confidence: 99%
“…We have investigated the seedling development and establishment of plantain and found that it establishes easily from seed (Sanderson and Elwinger, 2000a,b). There are some reports of medicinal attributes for plantain, such as anthelmintic properties, but the research is not conclusive (Knight et al, 1996; Gustine et al, 2001).…”
mentioning
confidence: 99%
“…The variation in postweaning and between-year growth rate appeared to coincide with changed proportions of clover and clover and chicory in swards (Table 6) and may reflect the higher nutritive value of these species. (Konolong et al 1992;Scales 1993;Scale et al 1995;Knight et al 1996). The proportion of clover and chicory declined Proceedings of the New Zealand Grassland Association 62: 59-66 (2000) Despite carcass weights consistently reflecting the rate of post-weaning liveweight gain such that the faster growing lambs produced the heavier carcasses, differences were not statistically significant between the Control and Improved treatments (Table 9).…”
Section: Animal Performancementioning
confidence: 97%